GMAT Question of the Day - Daily to your Mailbox; hard ones only

It is currently 12 Nov 2018, 21:05

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel
Events & Promotions in November
PrevNext
SuMoTuWeThFrSa
28293031123
45678910
11121314151617
18192021222324
2526272829301
Open Detailed Calendar
  • Essential GMAT Time-Management Hacks

     November 14, 2018

     November 14, 2018

     07:00 PM PST

     08:00 PM PST

    Join the webinar and learn time-management tactics that will guarantee you answer all questions, in all sections, on time. Save your spot today! Nov. 14th at 7 PM PST
  • $450 Tuition Credit & Official CAT Packs FREE

     November 15, 2018

     November 15, 2018

     10:00 PM MST

     11:00 PM MST

    EMPOWERgmat is giving away the complete Official GMAT Exam Pack collection worth $100 with the 3 Month Pack ($299)

If f(x) = 5 - 2x and f(3k) = f(k + 1), then f(k) =

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 50544
If f(x) = 5 - 2x and f(3k) = f(k + 1), then f(k) =  [#permalink]

Show Tags

New post 23 Oct 2018, 20:56
00:00
A
B
C
D
E

Difficulty:

  45% (medium)

Question Stats:

64% (01:31) correct 36% (01:33) wrong based on 44 sessions

HideShow timer Statistics

CEO
CEO
User avatar
P
Status: GMATINSIGHT Tutor
Joined: 08 Jul 2010
Posts: 2689
Location: India
GMAT: INSIGHT
WE: Education (Education)
Reviews Badge
If f(x) = 5 - 2x and f(3k) = f(k + 1), then f(k) =  [#permalink]

Show Tags

New post Updated on: 23 Oct 2018, 21:39
1
Bunuel wrote:
If f(x) = 5 - 2x and f(3k) = f(k + 1), then f(k) =

A. 0.5
B. 1
C. 3
D. 4
E. 6


f(x) = 5 - 2x

f(3k) = 5-2(3k) = 5 - 6k

f(k+1) = 5-2(k+1) = 3 - 2k

f(3k) = f(k + 1)

i.e 5 - 6k = 3 - 2k

i.e. k = 0.5

i.e. f(k) = 5-2(0.5) = 4

Answer: Option D
_________________

Prosper!!!
GMATinsight
Bhoopendra Singh and Dr.Sushma Jha
e-mail: info@GMATinsight.com I Call us : +91-9999687183 / 9891333772
Online One-on-One Skype based classes and Classroom Coaching in South and West Delhi
http://www.GMATinsight.com/testimonials.html

ACCESS FREE GMAT TESTS HERE:22 ONLINE FREE (FULL LENGTH) GMAT CAT (PRACTICE TESTS) LINK COLLECTION


Originally posted by GMATinsight on 23 Oct 2018, 21:09.
Last edited by GMATinsight on 23 Oct 2018, 21:39, edited 1 time in total.
Manager
Manager
avatar
S
Joined: 13 Jan 2018
Posts: 67
Location: India
GMAT 1: 580 Q47 V23
GPA: 4
Reviews Badge CAT Tests
Re: If f(x) = 5 - 2x and f(3k) = f(k + 1), then f(k) =  [#permalink]

Show Tags

New post 23 Oct 2018, 21:34
Hi GMATinsight

The question is asking for f(k) not for k value.

K is \(\frac{1}{2}\)

So f(k) = 5-2(\(\frac{1}{2}\))

f(k) = 5-1 => 4

OPTION : D
Intern
Intern
avatar
B
Joined: 23 Oct 2018
Posts: 6
GMAT 1: 760 Q50 V42
If f(x) = 5 - 2x and f(3k) = f(k + 1), then f(k) =  [#permalink]

Show Tags

New post 23 Oct 2018, 21:54
1
The first thing to notice here is that we’re solving for \(f(k)\), not \(k\) itself. Make a note, circle it, underline it, do whatever you need to do to remind yourself what you’re actually solving for!

The next step is to see that we’re given \(f(3k) = f(k+1)\). Let’s simplify by “getting rid” of these functions and plug in the values provided, which are \(3k\) and \(k+1\).

Given that \(f(x) = 5 - 2x\), we get:

\(5-2(3k)\) = \(5-2(k+1)\)

Solving, we get:

\(5-6k = 5-2k-2\)

\(-4k = -2\)

\(k = 1/2\)

Choice A is a trap! Remember that we’re solving for \(f(k)\), not \(k\). Let’s plug our \(k\) value back into \(f(x)\).

\(f(1/2) = 5 - 2(1/2) = 4\)

Answer D.
e-GMAT Representative
User avatar
P
Joined: 04 Jan 2015
Posts: 2173
Re: If f(x) = 5 - 2x and f(3k) = f(k + 1), then f(k) =  [#permalink]

Show Tags

New post 24 Oct 2018, 02:55

Solution


Given:
    • f(x) = 5 – 2x
    • f(3k) = f(k + 1)

To find:
    • The value of f(k)

Approach and Working:
    • f(3k) = 5 – 2(3k) = 5 – 6k
    • f(k + 1) = 5 – 2(k + 1) = 3 – 2k
    • We are given, f(3k) = f(k + 1)
      o Implies, 5 – 6k = 3 – 2k
      o Thus, \(k = \frac{1}{2}\)
    • Therefore, f(k) = \(5 – 2(\frac{1}{2}) = 4\)

Hence, the correct answer is Option D.

Answer: D

Image

_________________








Register for free sessions
Number Properties | Algebra |Quant Workshop

Success Stories
Guillermo's Success Story | Carrie's Success Story

Ace GMAT quant
Articles and Question to reach Q51 | Question of the week

Must Read Articles
Number Properties – Even Odd | LCM GCD | Statistics-1 | Statistics-2
Word Problems – Percentage 1 | Percentage 2 | Time and Work 1 | Time and Work 2 | Time, Speed and Distance 1 | Time, Speed and Distance 2
Advanced Topics- Permutation and Combination 1 | Permutation and Combination 2 | Permutation and Combination 3 | Probability
Geometry- Triangles 1 | Triangles 2 | Triangles 3 | Common Mistakes in Geometry
Algebra- Wavy line | Inequalities

Practice Questions
Number Properties 1 | Number Properties 2 | Algebra 1 | Geometry | Prime Numbers | Absolute value equations | Sets



| '4 out of Top 5' Instructors on gmatclub | 70 point improvement guarantee | www.e-gmat.com

Intern
Intern
avatar
Joined: 24 Oct 2018
Posts: 10
Re: If f(x) = 5 - 2x and f(3k) = f(k + 1), then f(k) =  [#permalink]

Show Tags

New post 24 Oct 2018, 06:40
K is 1212

So f(k) = 5-2(1212)

f(k) = 5-1 => 4

D
Target Test Prep Representative
User avatar
P
Status: Founder & CEO
Affiliations: Target Test Prep
Joined: 14 Oct 2015
Posts: 4155
Location: United States (CA)
Re: If f(x) = 5 - 2x and f(3k) = f(k + 1), then f(k) =  [#permalink]

Show Tags

New post 28 Oct 2018, 17:20
Bunuel wrote:
If f(x) = 5 - 2x and f(3k) = f(k + 1), then f(k) =

A. 0.5
B. 1
C. 3
D. 4
E. 6


We are given that f(x) = 5 - 2x. So f(3k) = 5 - 2(3k) = 5 - 6k and f(k + 1) = 5 - 2(k + 1) = 3 - 2k. Since f(3k) = f(k + 1), we equate the two expressions, and thus:

5 - 6k = 3 - 2k

2 = 4k

0.5 = k

Therefore, f(k) = f(0.5) = 5 - 2(0.5) = 4.

Answer: D
_________________

Scott Woodbury-Stewart
Founder and CEO

GMAT Quant Self-Study Course
500+ lessons 3000+ practice problems 800+ HD solutions

GMAT Club Bot
Re: If f(x) = 5 - 2x and f(3k) = f(k + 1), then f(k) = &nbs [#permalink] 28 Oct 2018, 17:20
Display posts from previous: Sort by

If f(x) = 5 - 2x and f(3k) = f(k + 1), then f(k) =

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  


Copyright

GMAT Club MBA Forum Home| About| Terms and Conditions and Privacy Policy| GMAT Club Rules| Contact| Sitemap

Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne

Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.